Reducing the harms of xylazine: clinical approaches, research deficits, and public health context - Claire M. Zagorski; Rebecca A. Hosey; Christopher Moraff; Aaron Ferguson; Mary Figgatt; Shoshana Aronowitz; Natalie E. Stahl; Lucas G. Hill; Zoe McElligott; Nabarun Dasgupta (BMC, 2023)
Abstract Objectives Xylazine has emerged as a consistent part of the unregulated drug supply in recent months. We discuss major domains of xylazine's harm, current knowledge deficits, clinical and harm reduction strategies for minimizing harm, and xylazine's public health and policy context. As an interdisciplinary team from across the USA, we have pooled our knowledge to provide an overview of xylazine's current and emerging contexts. Methods To inform this essay, the pertinent literature was reviewed, clinical knowledge and protocols were shared by multiple clinicians with direct expertise, and policy and public health context were added by expert authors. Results We describe xylazine's major harm domains-acute poisoning, extended sedation, and wounds, along with anemia and hyperglycemia, which have been reported anecdotally but lack as clear of a connection to xylazine. Current successful practices for xylazine wound care are detailed. Understanding xylazine's epidemiology will also require greater investment in drug checking and surveillance. Finally, approaches to community-based wound care are discussed, along with an orientation to the larger policy and public health context. Conclusions Addressing the harms of xylazine requires interdisciplinary participation, investment in community-based harm reduction strategies, and improved drug supply surveillance. The relatively unique context of xylazine demands buy-in from public health professionals, harm reduction professionals, clinicians, basic science researchers, policymakers and more.